2015
DOI: 10.1001/jamainternmed.2014.6786
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glomerular Kidney Function Among HIV-1Uninfected Men and Women Receiving EmtricitabineTenofovir Disoproxil Fumarate Preexposure Prophylaxis

Abstract: IMPORTANCE Tenofovir disoproxil fumarate (TDF) use has been associated with declines in the estimated glomerular filtration rate (eGFR) when used as part of antiretroviral treatment by persons with human immunodeficiency virus (HIV) type 1, but limited data are available for risk when used as preexposure prophylaxis (PrEP) for HIV-1 prevention.OBJECTIVE To determine whether TDF-based PrEP causes eGFR decline in HIV-1-uninfected adults. DESIGN, SETTING, AND PARTICIPANTSA per-protocol safety analysis of changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
71
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 37 publications
8
71
2
Order By: Relevance
“…As reported previously 10 , TDF and FTC-TDF use was associated with a small, nonprogressive decline in eGFR, and in the current analysis crude mean eGFR was 2-3 mL/min/1.73 m 2 lower in the active PrEP arms (representing annual eGFR loss of ≤1 mL/min/1.73 m 2 per year) compared to placebo at the last on-study drug visit: 129 mL/min/1.73 m 2 for TDF and 128 mL/min/1.73 m 2 for FTC-TDF versus 131 mL/min/1.73 m 2 for placebo (Table 2; p<0.01 for both TDF and FTC-TDF vs placebo). By 4 weeks after study drug discontinuation, mean eGFR were similar across the three groups (Figure): 130.1 mL/min/1.73 m 2 for TDF, 129.9 mL/min/1.73 m 2 for FTC-TDF, and 130.1 mL/min/1.73 m 2 for placebo (p>0.05 for both TDF and FTC-TDF vs placebo).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As reported previously 10 , TDF and FTC-TDF use was associated with a small, nonprogressive decline in eGFR, and in the current analysis crude mean eGFR was 2-3 mL/min/1.73 m 2 lower in the active PrEP arms (representing annual eGFR loss of ≤1 mL/min/1.73 m 2 per year) compared to placebo at the last on-study drug visit: 129 mL/min/1.73 m 2 for TDF and 128 mL/min/1.73 m 2 for FTC-TDF versus 131 mL/min/1.73 m 2 for placebo (Table 2; p<0.01 for both TDF and FTC-TDF vs placebo). By 4 weeks after study drug discontinuation, mean eGFR were similar across the three groups (Figure): 130.1 mL/min/1.73 m 2 for TDF, 129.9 mL/min/1.73 m 2 for FTC-TDF, and 130.1 mL/min/1.73 m 2 for placebo (p>0.05 for both TDF and FTC-TDF vs placebo).…”
Section: Resultssupporting
confidence: 76%
“…The World Health Organization and the US Centers for Disease Control and Prevention recommend TDF-based PrEP as part of a comprehensive package to prevent HIV infection in high-risk individuals 5,6 . Although generally well tolerated, TDF exposure has been associated with small but statistically significant decline in estimated glomerular filtration rate (eGFR) in HIV infected adults receiving TDF-containing antiretroviral regimens 7-9 and in HIV uninfected persons receiving TDF-based PrEP for HIV prevention 10,11 . Among HIV infected adults, kidney function returns to baseline level in a majority who discontinue TDF, but cases of less than optimal recovery have been reported 9,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Small declines in eGFR after TDF initiation were again seen [32, 33]. A drawback is the limited duration of TDF use in these PreP studies to date, in conjunction with a short follow-up time.…”
Section: Tolerability and Toxicitymentioning
confidence: 99%
“…In the D:A:D study cohort of HIV-infected patients (22 603 HIV-infected patients with baseline estimated glomerular filtration rate (eGFR) 90 ml/min per 1.73 m 2 ), tenofovir exposure was associated after adjustment with an increased relative risk (1.18 a year) of developing chronic kidney disease (CKD) defined by the occurrence of an eGFR below 70 ml/min per 1.73 m 2 [1]. Recent studies also suggested that tenofovir use in preexposure prophylaxis might also be associated with a weak decline in eGFR, a mean decrease in eGFR after 60 months of treatment was 6 ml/min in the Bangkok Tenofovir study [2], and around 2 ml/min per 1.73 m 2 during a median follow-up of 18 months in Partners Prep Study [3]. The decline in eGFR associated with tenofovir use is not always reversible after treatment cessation [4].…”
mentioning
confidence: 99%